2021
DOI: 10.1007/s10479-020-03904-1
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic programming model for an energy planning problem: formulation, solution method and application

Abstract: The paper investigates national/regional power generation expansion planning for medium/longterm analysis in the presence of electricity demand uncertainty. A two-stage stochastic programming is designed to determine the optimal mix of energy supply sources with the aim to minimise the expected total cost of electricity generation considering the total carbon dioxide emissions produced by the power plants.Compared to models available in the extant literature, the proposed stochastic generation expansion model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The integrated assessment model suggested that the cost of implementation of CCS is a crucial parameter up to the year 2050, not in the year 2100 (Yang et al, 2021). The probabilistic risk assessment of CCS using fault tree analysis and analytical hierarchy process (Oraee‐Mirzamani et al, 2013) and stochastic energy planning model (Irawan et al, 2021) are studied in the literature to reduce emissions. The comparative studies on two technologies, CCS and CCU, are examined in the article of Arning et al (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The integrated assessment model suggested that the cost of implementation of CCS is a crucial parameter up to the year 2050, not in the year 2100 (Yang et al, 2021). The probabilistic risk assessment of CCS using fault tree analysis and analytical hierarchy process (Oraee‐Mirzamani et al, 2013) and stochastic energy planning model (Irawan et al, 2021) are studied in the literature to reduce emissions. The comparative studies on two technologies, CCS and CCU, are examined in the article of Arning et al (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is common that uncertain parameters are tackled by the scenario tree configuration or Monte Carlo simulation. The two-stage stochastic programming model is studied by, among others, Krukanont and Tezuka (2007), Feng and Ryan (2013), Park and Baldick (2015), Irawan et al (2022), and Kim et al (2021). The multi-stage stochastic programming can be considered the most popular tool to solve the GEP under uncertainty.…”
Section: Introductionmentioning
confidence: 99%